2015
DOI: 10.1136/oemed-2015-102961
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of deployed UK maritime forces

Abstract: ObjectivesTo establish the level of psychological symptoms and the risk factors for possible decreased mental health among deployed UK maritime forces.MethodsA survey was completed by deployed Royal Navy (RN) personnel which measured the prevalence of common mental disorder (CMD), post-traumatic stress disorder (PTSD) and potential alcohol misuse. Military and operational characteristics were also measured including exposure to potentially traumatic events, problems occurring at home during the deployment, uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…In conclusion, Whybrow et al 1 have documented a surprisingly high prevalence of MHPs in Royal Navy personnel deployed at sea on missions with low exposure to traumatic stress, highlighting the role of non-traumatic workplace stressors in this environment. The strongest modifiable risk factors were leadership, morale, and cohesion, which point towards the potential benefits of organisational interventions targeting leader behaviours.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…In conclusion, Whybrow et al 1 have documented a surprisingly high prevalence of MHPs in Royal Navy personnel deployed at sea on missions with low exposure to traumatic stress, highlighting the role of non-traumatic workplace stressors in this environment. The strongest modifiable risk factors were leadership, morale, and cohesion, which point towards the potential benefits of organisational interventions targeting leader behaviours.…”
mentioning
confidence: 83%
“…Fewer still have looked at deployed sailors, so Whybrow et al 's1 cross-sectional survey of MHPs among Royal Navy personnel deployed at sea is a welcome addition to the literature. They found that 41.2% had common mental disorder symptoms (ie, mood, anxiety or neurotic spectrum disorders), 7.8% probable post-traumatic stress disorder (PTSD), and 17.4% potentially harmful alcohol use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Alcohol Use Disorders Identification Test -Consumption (AUDIT-C; Bush et al, 1998) was used to assess alcohol consumption. This brief validated screening tool has been used in several contemporary studies involving workers in 'high-stress' occupations, such as military personnel (Whybrow et al, 2016), firefighters (Piazza-Gardner et al, 2014), veterinary surgeons (Bartram et al, 2009), and emergency department staff (Nordqvist ERI AND ALCOHOL 8 et al, 2004). The measure includes three questions (α = .65) concerning the frequency and quantity of alcohol consumption: "How often do you have a drink containing alcohol?"…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Dichotomisation was undertaken because (i) the AUDIT-C instrument was designed to identify 'at risk' individuals, which is desirable in the context of research that seeks to inform the design of tailored and targeted workplace health promotion interventions, (ii) skew and kurtosis scores violated parametric assumptions thereby hindering the application of hierarchical linear regression, and (iii) dichotomisation of AUDIT-C scores is common practice in the occupational health scientific literature (e.g., Bartram et al, 2009;Dawson et al, 2005;Neumann et al, 2012;Nordqvist et al, 2004;Piazza-Gardner et al, 2014;Whybrow et al, 2016) and therefore facilitated comparison of findings from the current study with those conducted among other 'high stress' occupational groups. Tuunanen et al (2007) recommend that cut-off scores for the identification of heavy consumption should be tailored to the populations under examination; following precedent (Aalto et al, 2009;Dawson et al, 2005;Neumann et al, 2012), scores ≥ 6 in men and ≥ 4 in women identified heavy drinking.…”
Section: Dependent Variablesmentioning
confidence: 99%